Sistem Informasi Sekolah Berbasis Web pada SD 08 Nan Limo Mudik - Mainetri, Padina (Journal of Information System and Education Development, 2025)
This study aims to design, build and implement a Web-Based School Information System at State Elementary School (SDN) 08 Nan Limo Mudik. The research method used is the system development method with the Waterfall model. Data collection techniques use interview methods, observation and library techniques. The Web-Based School Information System at State Elementary School (SDN) 08 Nan Limo Mudik in its design uses the UML (Unified Modeling Language) development method consisting of Use Case Diagrams, Activity Diagrams, Sequence Diagrams and Class Diagrams. The database design uses MySQL and the system interface. The software used in the design and implementation of the system uses XAMPP as a webserver, PHP and MySQL as a database. The Web-Based School Information System includes, login page, home page, profile page, student page, gallery, agenda page, student registration page, contact page, profile management page, student management page, gallery management page, agenda management page, registration page. The information system has been tested (test case) so that a well-running information system is obtained